Characterization of a Large Panel of Lactic Acid Bacteria Derived from the Human Gut for their Capacity to Polarize Dendritic Cell - Chistensen, H. R. (Scand J Immunol, 2008)
Dendritic cells (DCs) are the principal stimulators of naïve T helper (Th) cells and play a pivotal regulatory role in the Th1, Th2 and Treg cell balance. DCs are present in the gut mucosa and may thus be target for modulation by gut microbes, including ingested probiotics. Here, we tested the hypothesis that species of lactic acid bacteria, important members of the gut flora, differentially activate DC. A large panel of human gut‐derived Lactobacillus and Bifidobacterium spp. was screened for DC‐polarizing capacity by exposing bone marrow‐derived murine DC to lethally irradiated bacteria. Cytokines in culture supernatants and DC‐surface maturation markers were analysed. Substantial differences were found among strains in the capacity to induce interleukin‐12 (IL‐12) and tumour necrosis factor (TNF)‐α, while the differences for IL‐10 and IL‐6 were less pronounced. Bifidobacteria tended to be weak IL‐12 and TNF‐α inducers, while both strong and weak IL‐12 inducers were found among the strains of Lactobacillus. Remarkably, strains weak in IL‐12 induction inhibited IL‐12 and TNF‐α production induced by an otherwise strong cytokine‐inducing strain of Lactobacillus casei, while IL‐10 production remained unaltered. Selected strains were tested for induction of DC maturation markers. Those lactobacilli with greatest capacity to induce IL‐12 were most effective in upregulating surface MHC class II and CD86. Moreover, L. casei‐induced upregulation of CD86 was reduced in the presence of a weak IL‐12‐inducing L. reuteri. In conclusion, human Lactobacillus and Bifidobacterium spp. polarize differentially DC maturation. Thus, the potential exists for Th1/Th2/Treg‐driving capacities of the gut DC to be modulated according to composition of gut flora including ingested probiotics.